Effect of banana peels (Musa Paradisiaca cv Awak) as growth promoting substance in Phalaenopsis Amabilis orchid in vitro culture - Siti Salwa Abdul Ghani @ Che Omar (2022)
Natural additives from agriculture waste remain largely untapped in enhancing germination, micropropagation, and growth of many orchids, especially Phalaenopsis amabilis species that are highly demanded. Interestingly total phytochemical compounds, especially antioxidants, had been discovered abundant in banana peels in general. This research mainly aimed to study the effects of various concentrations of Musa paradisiaca cv. Awak banana peels as a natural additive towards Phalaenopsis amabilis orchid multiplication since fruit peels were mostly discarded as waste. This study consists of three factors: (i) Murashige and Skoog (MS) basal media as negative control (ii) MS medium supplement with commercial plant growth regulator 1 mg/1 of 6-Benzylaminopurine (BAP) with 1 g/I activated charcoal as positive control and (iii) MS medium supplemented with three different concentrations of banana peel (5, 10 and 20% [w/v]) that focus on the effect of the natural additive on multiplication stage. Data recorded as growth performances included the root number, root length, leaf number, leaf width, height, and survival frequency of explant. From the highest mean, leaves number (3.47 ± 0.22), leaves length (1.50 ± 0.07 cm), leaves width (0.93 ± 0.03 cm), the height of explant (0.58 ± 0.02 cm), and root number (2.33 ± 0.12) by 20% banana peels media while closely followed by the second highest by positive control (1 mg/I of BAP+1g/I of active charcoal). All treatments showed there was no contamination occurring after 2 months at the sub-culturing stage. The recommended natural additive of explant Phalaenopsis amabilis orchid was 20 % banana peels which could be considered as an alternative supplement culture for Phalaenopsis amabilis orchid growth. Hence, the banana peel homogenate might be gain insights in potential as a supplement in culture media for tissue culture studies and also convey that fruits waste can be attained by converting peels into a valuable product